PENGARUH JOB SATISFACTION TERHADAP OCB DAN TURNOVER INTENTION - Ningsih, Febru Rida; Arsanti, Tutuk Ari (Benefit, 2014)
This article aims to provide the impact of job satisfaction to OCB and turnover intention. This study used a quantitative method with a statistical analysis. Simple analysis regression used to test each hypotheses. The object of this research is a branch of national bank. Population in this research are entire employees of a brach of national bank that is e non frontliner employees. Non-probability sampling is used of this reseach. The measurement of job satiafaction and turnover intention variables used likert scale that developed by Rinaldi (2008) and measurement of OCB variable adopted from  Organ (1988).  The result of this research has shown that hypotheses one is rejected and hypotheses two is accepted. Eventually, through this article, an understanding that job satisfaction does not significantly influence to OCB but job satisfaction has significant influence to turnover intention.